Toys Are Us: Sex Toys, Substantive Due Process, and the American Way - Waldo, Curtis (Columbia Journal of Gender and Law, 2009)
In the six years since the Supreme Court decided Lawrence v. Texas,I circuit courts have disagreed over the proper standard of review for statutes that implicate sexual privacy. Two cases stand out: Williams v. Attorney General of Alabama, from the Eleventh Circuit in 2004, and Reliable Consultants v. Earle, from the Fifth Circuit in 2008. In Williams, the court upheld an Alabama statute that prohibited the sale of sex toys; in Reliable, the court struck down a Texas statute with similar wording. The judges in both cases, whether writing for the majority or for the dissent, measured the statutes against Justice Kennedy’s opinion in Lawrence, but their interpretations differed in significant respects. The majority in Williams, along with the dissent in Reliable, thought Lawrence required rational basis review and that the sex toy statute would easily pass. Conversely, the dissent in Williams believed that the Alabama statute should be assessed under strict scrutiny but that it would fail even rational basis review. Finally, the majority in Reliable was careful to apply neither rational basis nor strict scrutiny, instead simply “apply[ing] Lawrence.” After Lawrence, those who have written about the circuit courts’ treatment of sex toy statutes have generally focused on the right to sexual privacy threatened by these bans, which they contend that the majority in Williams and the dissent in Reliable failed to appreciate. However, this Article will argue that the circuit courts’ disagreement in Williams and Reliable is a result of the courts’ continued, but misguided, practice of evaluating the nature of the right asserted by the claimant. Lawrence should be regarded as a retreat from this practice. The Lawrence Court, after finding that the statute at issue addressed a relationship that was outside the proper realm of state action, struck it down as prohibiting activity which was “within the liberty of persons to choose. What Lawrence left unresolved was how future courts should determine when state action impermissibly treads upon this “liberty.” That is the problem which this Article aims to solve.